Keadilan organisasional dan konsekuensinya - Marso, Marso; Anggreyani, Mince (Jurnal Manajemen Maranatha, 2024)
This study was conducted to develop a structural equation model to examine the relationships between organizational justice, job satisfaction, and organizational commitment. A sample of 93 respondents was selected using a non-probability sampling approach. The evaluation of the measurement model was conducted to test the validity and reliability of the instruments, while the structural model evaluation for hypothesis testing was performed using the SmartPLS software. The findings reveal that organizational justice has a significant influence on both job satisfaction and organizational commitment. Job satisfaction has a positive and significant effect on organizational commitment. Job satisfaction not only serves as a consequence of organizational justice and a precursor to organizational commitment, but it also partially mediates the impact of organizational justice on organizational commitment. Theoretically, these findings make a valuable contribution to the development of justice theory, job satisfaction theory, and organizational commitment theory. Practically, the results of this study provide useful guidance for hotel management in designing policies aimed at increasing employees' organizational commitment through effective management of organizational justice.